Simplified [F]FDG Image-Derived Input Function Using the Left Ventricle, Liver, and One Venous Blood Sample - Mohammed Noor Tantawy; Todd E. Peterson (Molecular Imaging, 2010)
A relatively simple, almost entirely noninvasive imaging-based method is presented for deriving arterial blood input functions for quantitative [ 18 F]2-fluoro-2-deoxy- d -glucose (FDG) positron emission tomographic (PET) studies in rodents. It requires only one venous blood sample at the end of the scan. MicroPET images and arterial blood time-activity curves (TACs) were downloaded from the Mouse Quantitation Program database at the University of California, Los Angeles. Three-dimensional regions of interest were drawn around the blood-pool region of the left ventricle and within the liver to derive their respective TACs. To construct the “hybrid” image-derived input function (IDIF), the initial part of the left ventricle TAC, containing the peak concentration of [ 18 F]FDG in the arterial blood, was corrected for spillout (ie, partial-volume effect yielding a recovery coefficient < 1) and then joined to the liver TAC (normalized to the 60-minute arterial blood sample) immediately after it peaks. To validate our method, the [ 18 F]FDG influx constant (K i ) was estimated using a two-tissue compartment model and compared to estimates of K i obtained using measured arterial blood TACs. No significant difference in the K i estimates was obtained with the arterial blood input function and our hybrid IDIF. We conclude that the normalized hybrid IDIF can be used in practice to obtain reliable K i estimates.